Temperament, Emotion, and Childhood Stuttering - Jones, Robin; Choi, Dahye; Conture, Edward; Walden, Tedra (Seminars in Speech and Language, 2014)
Reactivity refers to arousal of emotions, motor activity, and attention, and self-regulation refers to the ability to moderate those tendencies. In general, temperament is typically thought of as an individual's constitutionally (biologically) based behavioral proclivities. These proclivities often include emotional reactivity and self-regulation. Reactivity refers to arousal of emotions, motor activity, and attention, and self-regulation refers to the ability to moderate those tendencies. The traitlike nature of temperament makes it potentially salient to our understanding of the onset and development of stuttering because temperamental tendencies may result in greater reactivity or difficulty in coping. Emotions, which are more statelike and variable, may influence the variation of stuttering commonly observed both within and between speaking situations. Temperament and emotion may serve as a causal contributor to developmental stuttering, with empirical findings indicating that preschool-aged children who stutter (CWS) exhibit differences in temperament and emotion when compared with children who do not stutter. Given that empirical study of temperament in preschool-aged CWS is nascent, extensive discussion of clinical implications is challenging. With that caution, we present some early possibilities, including matching treatment approaches with the child's temperamental profile and using temperament as a predictor of treatment outcome.
Keywords: Stuttering; childhood; temperament; emotion; development; treatment